Birth Stories of Trinidad and Tobago: Ava-Dawn Alexander Lewis - (:unkn) unknown (The University of the West Indies, 2024)
Ava is a stay at home mother of three children. Her oldest child who is twelve years old, was born at Gulf View Medical Centre, La Romain. For the second child she had her second child at the Center. Her third child was born at home.
Keywords: Childbirth -- Trinidad and Tobago